Bonded Excimer in Stacked Cytosines: A Semiclassical Simulation Study - Weifeng Wu; Shuai Yuan; Jiajie She; Yusheng Dou; Roland E. Allen (International Journal of Photoenergy)
The formation of a covalent bond between two stacked cytosines, one of which is excited by an ultrafast laser pulse, was studied by semiclassical dynamics simulations. The results show that a bonded excimer is created, which sharply lowers the energy gap between the LUMO and HOMO and consequently facilitates the deactivation of the electronically excited molecule. This is different from the case of two stacked adenines, where the formation of a covalent bond alters the nonadiabatic deactivation mechanism in two opposite ways. It lowers the energy gap and consequently leads to the coupling between the HOMO and LUMO levels, thus enhancing the deactivation of the electronically excited molecule. On the other hand, it leads to restriction of the deformation vibration of the pyrimidine in the excited molecule, because of a steric effect, and this delays the deactivation process of the excited adenine molecule with return to the electronic ground state.